Intra-Amnionic Threonine Administered to Chicken Embryos Reduces Salmonella Enteritidis Cecal Counts and Improves Posthatch Intestinal Development - Alexandre L. de B. Moreira Filho; Celso J. B. Oliveira; Oliveiro C. Freitas Neto; Candice M. C. G. de Leon; Mauro M. S. Saraiva; Maria F. S. Andrade; Bryan White; Patrícia E. N. Givisiez (Journal of Immunology Research)
This study assessed the effect of in ovo threonine supplementation on the response of broiler chicks challenged with Salmonella Enteritidis, considering bacterial counts in cecal contents, intestinal morphology, body weight, and weight gain. Fertilized eggs were inoculated in the amniotic fluid with saline (NT) or 3.5% threonine (T) solution at day 17.5 of incubation. At hatch, chicks were individually weighed and cloacal swabs were screened for Salmonella. At 2 days of age, half of the birds from each in ovo treatment were given either 0.5 mL of nutrient broth (sham-inoculated) or nalidixic acid-resistant Salmonella Enteritidis (SE NalR) in nutrient broth (8.3 × 107 colony forming units (CFU) SE NalR/mL). The birds were distributed using a completely randomized design with four treatments after the Salmonella challenge: no in ovo Thr supplementation and sham-inoculated in the posthatch challenge (NT-SHAM), in ovo Thr supplementation and sham-inoculated (T-SHAM), no in ovo Thr supplementation and SE NalR-challenged (NT-SE), and in ovo Thr supplementation and SE NalR-challenged (T-SE). In ovo threonine supplementation reduced Salmonella Enteritidis colonization 168-hour postinoculation and reduced the negative effects associated with Salmonella infection on intestinal morphology and performance, with results similar to those of the sham-inoculated birds. In ovo Thr supplementation increased the expression of MUC2 at hatch and the expression of MUC2 and IgA at 2 days of age and 168-hour postinoculation. Our results suggest that providing in ovo threonine promotes intestinal health in broilers challenged with Salmonella Enteritidis in the first days of life.